Photochromism of dihydroindolizines Part XIX. Efficient one‐pot solid‐state synthesis, kinetic, and computational studies based on dihydroindolizine photochromes†. (25th July 2016) - Ahmed, Saleh A.; El Guesmi, Nizar; Asghar, Basim H.; Maurel, François; Althagafi, Ismail I.; Khairou, Khalid S.; Muathen, Hussni A.
Abstract : For the first time, one‐pot solid‐state synthesis of 12 photochromic materials based on photochromic dihydroindolizine system substituted in both fluorene part (region A) and the heterocyclic part (region C) has been established. This method has immense advantages, which are short‐time reaction, high‐yield and low‐yield by‐products, and easily purification andseparation processes . In addition, this method will help in getting over the tremendously purification and low‐yield problems faced since the worth‐finding of this family of photochromic materials. The absorption maxima ( λ max ) and the half‐lives ( t 1 / 2 ) of the colored betaines were detected in all cases using multichannel UV/Vis spectrophotometric measurements. The rate constants of the thermal back reaction of the betaines were determined at constant temperature by measuring the decrease in the maximum absorption intensity ( λ max ) with time. The half‐lives ( t 1 / 2 ) and rate constants ( k ) of betaines under examination were calculated by plotting lnA against time ( t ). Thekinetic measurements could be detected by both spectra scan and time‐dependent decay measurements. Examination of the Arrhenius parameters reveals an underlying compensation between Ea and log A, whereby an increase in Ea is opposed by an increase in log A . The compensation appears in the corresponding Eyring parameters, Δ H ≠ and Δ S ≠ ; betaine structural changes that lead to lower, more favorable enthalpies of activation engender opposing entropic changes. At the isokinetic temperature T iso = β, structural changes do not affect the rate constant of a reaction series because the changes of Δ H ≠ are counterbalanced by changes of Δ S ≠ . The existence of an isokinetic relationship indicates a common structure of the transition state of all thermal back reaction of betaine under investigation. The computational results suggest that the decoloration reaction is a two‐step mechanism. The first step corresponds to the transoid–cisoidisomerization with an activation barrier of 10.3 kJ mol −1, and the second step is the ring closure from the cisoidintermediate with a barrier 71.3 kJ mol −1, which represent the rate determining step for thermal decoloration. Thephotochemical ring opening of DHIs to betaines is a disrotatory 1, 5‐electrocyclic reaction, whereas the thermal ring‐closing occurs in the conrotatory mode. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The computational and experimental results suggest that the decoloration reaction is a two‐step mechanism. The first step corresponds to the transoid‐cisoid isomerization with an activation barrier of 10.3 kJ mol −1, and the second step is the ring closure from the cisoid intermediate with a barrier of 71.3 kJ mol −1, which represents the rate‐determining step for thermal decoloration.